Serum Anti-Mullerian Hormone, New Marker in Diagnosis of Polycystic Ovarian Syndrome among Women of Reproductive Age (KYAMC Journal, 2026)
Background: Polycystic ovarian syndrome (PCOS) affects up to one-fifth of women of reproductive age and causes anovulatory subfertility. Serum AMH (Anti-Mullerian Hormone) levels are stable throughout menstrual cycle, and are unmodified by pregnancy, gonadotropin-releasing hormone treatment and administration of short-term oral contraceptives. These make AMH an ideal marker of ovarian reserve.Objective: To analyze serum AMH levels among PCOS women of reproductive age to use AMH as a biomarker predictor along with other Rotterdam criteria.Materials and Methods: In this cross-sectional study, a total of 200 women visiting in Gynae word at Combined Military Hospital, Dhaka were screened. Data were obtained from 100 normal healthy control and 100 newly diagnosed PCOS women aged 28.24 years (SD±4.84 years) meeting at least two of the Rotterdam criteria and specific inclusion criteria. Baseline variables, menstrual cycle length, hirsutism, sex hormones, TSH and serum AMH levels were analyzed during the follicular phase (1–5 days) of the menstrual cycle. Serum AMH was measured by electro chemiluminometric assay in Cobas 6000.Results: A high serum AMH level (7.23±4.67 ng/ml) was recorded with normal sex hormone levels in PCOS patients. Women with PCOS had a significant mean deference for luteinizing hormone (p=0.04) and AMH levels (p=0.03) when compared with women of normal healthy control. Among PCOS patients BMI, oligomenorrhoea and infertility rate are more common than healthy controls.Conclusion: An elevated serum AMH level can be used as a strong predictor to reflect the certainty of PCOS diagnosis among women of reproductive age when study concurrently with the other Rotterdam criteria.KYAMC Journal Vol. 16, No. 03, October 2025: 108-114.